2021
DOI: 10.3389/fphar.2021.653940
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity in Diabetic Wound Healing: Focus on the Mastermind Hidden in Chronic Inflammatory

Abstract: A growing body of evidence suggests that the interaction between immune and metabolic responses is essential for maintaining tissue and organ homeostasis. These interacting disorders contribute to the development of chronic diseases associated with immune-aging such as diabetes, obesity, atherosclerosis, and nonalcoholic fatty liver disease. In Diabetic wound (DW), innate immune cells respond to the Pathogen-associated molecular patterns (PAMAs) and/or Damage-associated molecular patterns (DAMPs), changes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 208 publications
(237 reference statements)
0
35
0
Order By: Relevance
“…M φ derived from monocytes participates in each phase of the wound healing process because they kill pathogenic microbes, remove damaged tissue, and produce growth factors [ 48 ]. In response to complex microenvironments and molecular mediators, M φ is polarized into the classical pr-inflammatory M1 or alternative anti-inflammatory M2 [ 49 ]. The orderly transition from M1 to M2 results in beneficial effects on wound healing, particularly in tissue remodeling and angiogenesis [ 50 ].…”
Section: Main Factors Involved In the Pathogenesis Of Diabetic Woundmentioning
confidence: 99%
See 1 more Smart Citation
“…M φ derived from monocytes participates in each phase of the wound healing process because they kill pathogenic microbes, remove damaged tissue, and produce growth factors [ 48 ]. In response to complex microenvironments and molecular mediators, M φ is polarized into the classical pr-inflammatory M1 or alternative anti-inflammatory M2 [ 49 ]. The orderly transition from M1 to M2 results in beneficial effects on wound healing, particularly in tissue remodeling and angiogenesis [ 50 ].…”
Section: Main Factors Involved In the Pathogenesis Of Diabetic Woundmentioning
confidence: 99%
“…In the DW state, chronic low-grade inflammation that persists indefinitely is a key cause of nonhealing of wounds [ 52 ], wherein M1 persists continuously and cannot transit to M2 phenotypes. In addition, Ganesh et al [ 53 ] found that the levels of proinflammatory cytokines, including interleukin-1 beta (IL-1 β ), tumor necrosis factor-alpha (TNF- α ), and interferon-gamma (IFN- γ ), are elevated in DW, which induces local hyperglycemia, accumulation of advanced glycation end products (AGEs), and ROS, along with an increase in chronic inflammation [ 49 ]. The same outcome has been observed in animal experiments, in which macrophages from normal mice switched from a pro- to anti-inflammatory phenotype on the tenth day, while diabetic mice displayed a twofold higher expression of proinflammatory factors IL-1 β and IFN- γ [ 54 ], which facilitated the maintenance of the proinflammatory M1 phenotype.…”
Section: Main Factors Involved In the Pathogenesis Of Diabetic Woundmentioning
confidence: 99%
“…The injury leads to the activation of the coagulation system, which successfully stops bleeding and provides the necessary matrix for the initiation of the inflammatory response. Tissue-resident cell surface pattern recognition receptors (PRRs) are recognized by Damage Associated Molecular Patterns (DAMPs) or Pathogen Associated Molecular Patterns (PAMPs), which in turn release specific chemokines and pro-inflammatory cytokines to recruit inflammatory cells ( 13 ). At the same time, the intracellular inflammatory signaling pathways, such as toll-like receptors (TLRs) and nuclear factor kappa B (NFκB) at the wound site are activated to trigger a signaling cascade ( 14 ).…”
Section: Inflammatory Phase Of Wound Healingmentioning
confidence: 99%
“…Over the last two decades, a wide body of literature has explored the mechanisms underlying the impaired WH occurring in both of these pathologic conditions. This has led to the identification of alterations in cells, cellular functions, molecular pathways, and molecules involved, all representing potential targets of innovative therapeutic strategies [79,80]. In particular, the prevailing current approach in studying the mechanisms underlying the physiological and pathological WH processes is that of focusing on the types/subtypes and functions of cells recruited or participating in the development and termination of the processes [17], as well as their possible qualitative or quantitative modifications leading to WH impairment and delay.…”
Section: Impaired Healing In Diabetes and Venous Stasis Ulcersmentioning
confidence: 99%